Establishment of legal awareness groups and legal extension of community social diseases for young generations in karang taruna amanah (Village Jati Rejo, Pagar Merbau district Deli Serdang district) - Yudhistira, Eko; kalo, Syafruddin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Community social problems such as gambling, drinking, drug abuse, which is hereinafter referred to as social disease, are a problem that will be continuously faced in big cities and in areas such as rural areas. These social ills are generally experienced by young people (productive age). This will certainly be a new obstacle for the progress of a nation. Young people who are in the productive age group will spend a lot of time and opportunity when they are involved in the social ills of the community. Therefore we need joint steps from the central government, regional government, private sector, community, family and others to find solutions to problems that occur. Community service activities in Jati Rejo Village, Pagar Merbau Sub-District, Deli Serdang Regency are intended to find out the development of social conditions in the village and provide legal counseling about community social ills to communities in Jati Rejo village with the hope that the community will be more introspective and aware not to be involved in various activities that are against the law.